S-NiFe2O4@graphene/cellulose nanofibers/polyvinyl alcohol composite towards high-performance microwave absorption and flame retardancy - Qiang Guo; Yanfei Pan; Shuaiqi Hu; Zhenghua Xue; Sufen Hao; Jintian Huang (Materials & Design)
Metal oxide matrix composites have received extensive attention as potential electromagnetic wave absorbing materials. Due to the imperfect magnetic/dielectric multi-component and structural adjustment, how to obtain materials with high electromagnetic wave absorption performance and integrated multifunctionality is quite challenging. In this study, S-NiFe2O4@graphene composites with adjustable vacancies, defects and Schottky interfaces were developed and encapsulated in cellulose nanofibers and polyvinyl alcohol to prepare S-NiFe2O4@graphene/CNF@PVA film. Cellulose nanofibers acts as a unique rib structure of the composite film to make it have excellent mechanical strength. The heterogeneous interface formed by the multi-component and the rich defects promote the balance between electromagnetic loss and impedance matching. S-NiFe2O4@graphene minimum reflection loss was −54.55 dB, and the absorption bandwidth was 2.2 GHz. The NF-4@G absorption bandwidth covers entire X-band at 0.9–1.1 mm thickness. Besides, the peak heat release rate and total heat release of the modified composite film were reduced by 67.83 % and 66.23 % and smoke release was also significantly reduced. The tensile strength and elongation at break were 8.32 MPa and 84.2 %. This work provides valuable insights for the development of multifunctional and reusable electromagnetic wave absorption materials.